The Robust Two-Echelon Inventory Routing Problem for Vaccine Supply System – A Heuristic Method - CHEN, Gang; JIANG, Yunjian; CHEN, Zhongyong; MA, Bingshan; SU, Luan (Promet - Traffic&Transportation, 2026)
Vaccine supply chains confront several challenges in guaranteeing security of vaccines from the phase of production to the injection. Thus, it is crucial to construct a robust vaccine supply system that helps store and deliver vaccines safely and effectively. Inspired by a real-world vaccine supply case, this paper studies a robust two-echelon inventory routing problem that integrates the optimisation of vendor managed inventory (VMI), inventory policy and vehicle routing. A deterministic model is formulated to jointly optimise two-echelon vehicle routes as well as inventory at both distribution warehouse and vaccine demand nodes. Then, a robust modelling approach is introduced and converted into an equivalent linear form. An efficient solution algorithm is proposed, merging simulated annealing (SA) and adaptive large neighbourhood search (ALNS) to address large-scale cases. The computational efficiency of the proposed algorithm is demonstrated through numerical comparisons to the solutions founded by CPLEX and ALNS. The relation between input parameters and optimised results is investigated by a real-world vaccine supply system. The findings from results and sensitivity analyses suggest some interesting managerial implications.